Deciphering the pharmacological potentials of Aganosma cymosa (Roxb.) G. Don using in vitro and computational methods. (March 2022) - Annadurai, Pushparaj; Gideon, Daniel A.; Nirusimhan, Vijay; Sivaramakrishnan, Ramachandran; Dhandayuthapani, Kandavel; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Aganosma cymosa Roxb. is a rare climber with antibrochitis & anthelmintic activity. Methanolic leaf extract has antioxidant, anti-inflammatory, antimicrobial, cytotoxic effects. Secondary metabolites – coprostanol, indole, pyrocatechol and 4-methyl catechol. Docking and dynamics of metabolites with key breast cancer proteins. At instances, the metabolites docked with better –ΔG than control cancer therapeutic compounds. Abstract: The methanolic leaf extract of A. cymosa yielded significant (60-75%) free radical scavenging activity in ABTS [2, 2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid)] and DPPH (2, 2'-diphenyl 1-picryl hydrazyl) assays, in the concentration range of 10-100 μg/mL. The extract showed antioxidant efficacy of 30-65% in reducing power assay and 55% inhibition in nitric oxide scavenging assay against ascorbic acid positive control. The plant extract exhibited modest inhibition against Escherichia coli, P se udomonas aeruginosa and the fungal strain, Echinodontium tinctorium . The IC50 value of the extract was 100 μg/mL against MCF-7 breast cancer cells in MTT assay. The extract yielded 22-65% inhibition at 100-800 μg/mL concentration range in RBC membrane stabilization assay. Qualitative phytochemical screening revealed the presence of several classes of primary and secondary metabolites. Quantitative analysis revealed a high content of phenolic and flavonoid molecules. GC-MS profile of the plant extract revealed the presence of 44 bioactive compounds. Network analysis of key breast cancer proteins from differentially expressed genes aided in selecting the key proteins involved in breast cancer pathophysiology. ADMET-SAR analysis was done to assess the potential bioactivity of selected compounds. From the molecular docking results, coprostanol, 4-methylcatechol, pyrocatechol and indole were found to act as ligands of breast cancer target proteins. Furthermore, in molecular dynamics simulations (50 ns), the receptor-ligand complexes were stable for 50 nanoseconds. The results indicate that coprostanol is the principal component for binding to the selected breast cancer receptor proteins. Together, the results suggest that the phytochemicals explored herein exert the beneficial biological activities of A. cymosa .